Vesicular stomatitis virus glycoprotein is necessary for H-2-restricted lysis of infected cells by cytotoxic T lymphocytes. - Hale, A H (1978)
Vesicular stomatitis virus (VSV) elicited cytotoxic thymus-derived lymphocytes (CTLs) in mice of the BALB/c and three congenic strains (BALB.b, BALB.k, BALB.HTG). CTL lysis of VSV-infected fibroblasts from the four strains was restricted by the target cells' major histocompatibility complex (H-2). Target cells were also infected with two temperature-sensitive mutants of VSV, tsM and tsG in which, respectively, the viral matrix protein and glycoprotein are not expressed at 39 degrees (restrictive temperature) on the infected cell's surface membrane. At the restrictive temperature, cells infected with wild-type VSV or tsM were lysed by CTLs, but cells infected with tsG were not. The requirement for the glycoprotein on the target cell was also evident from the ability of antisera to the glycoprotein to block completely CTL lysis of VSV-infected cells.